MULTIMODAL CONCEPTION IN LEARNING - Mochammad Bayu Firmansyah (Jurusan Sastra Indonesia, 2018)
This article aims to formulate a multimodal conception in the learning hierarchy. This exposure is based on three things, namely: (1) Multimodal definitions vary, (2) Higher education curriculum, and (3) Findings of research on multimodal utilization in learning. The problem relates to the pedagogical aspects of multimodal learning in the view of constructivism. 21st century learning requires learners to be proficient in interpreting text, discourse to socio-culture. This issue then inspects the multimodal conception in order to formulate multimodal learning as an approach.